2014
DOI: 10.5858/arpa.2013-0403-oa
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Napsin A Expression: A Potential Diagnostic Pitfall in Distinguishing Primary From Metastatic Mucinous Tumors in the Lung

Abstract: Context.-Napsin A is a useful marker for distinguishing primary from metastatic lung tumors. Mucinous lung tumors may be difficult to distinguish from metastatic mucinous tumors.Objectives.-To evaluate napsin A expression in lung and extrapulmonary mucinous tumors on both histology and cytology specimens and to determine napsin A's utility in differentiating primary from metastatic mucinous tumors.Design.-Napsin A immunohistochemistry was performed using a rabbit polyclonal antibody on formalinfixed, paraffin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In our laboratory, we noticed a particularly extensive, puzzling reactivity with p-Napsin A in mucinous adenocarcinomas of various sites, regardless of the site of origin. Such reactivity of p-Napsin A was also recently noted by Heymann et al, 5 but without confirmation of whether those tumors were negative for m-Napsin A. To address this issue we compared staining of p-Napsin A (Ventana/Cell Marque, Tucson, Arizona) and mNapsin A (clone IP64, Leica Biosystems/Novocastra, Buffalo Grove, Illinois) in whole-tissue sections from resected mucinous adenocarcinomas of lung (n ¼ 8) and extrapulmonary sites (n ¼ 13), including appendiceal, ovarian, colorectal, and pancreatic.…”
Section: Brad D Barrows Do Mssupporting
confidence: 78%
See 1 more Smart Citation
“…In our laboratory, we noticed a particularly extensive, puzzling reactivity with p-Napsin A in mucinous adenocarcinomas of various sites, regardless of the site of origin. Such reactivity of p-Napsin A was also recently noted by Heymann et al, 5 but without confirmation of whether those tumors were negative for m-Napsin A. To address this issue we compared staining of p-Napsin A (Ventana/Cell Marque, Tucson, Arizona) and mNapsin A (clone IP64, Leica Biosystems/Novocastra, Buffalo Grove, Illinois) in whole-tissue sections from resected mucinous adenocarcinomas of lung (n ¼ 8) and extrapulmonary sites (n ¼ 13), including appendiceal, ovarian, colorectal, and pancreatic.…”
Section: Brad D Barrows Do Mssupporting
confidence: 78%
“…It is possible that this high degree of nonspecific reactivity may be related to particular staining conditions in our laboratory, because in the two prior publications nonspecific reactivity of p-Napsin A in mucinous carcinomas was significant but not universal. 2,5 Of note, p-Napsin A staining was not entirely indiscriminate in our laboratory, because p-Napsin A did not label a large series of unrelated tumors, including squamous cell carcinomas, small cell carcinomas, and carcinoid tumors. 6 The reason for the affinity of p-Napsin A for mucinous neoplasms is not clear.…”
Section: Brad D Barrows Do Msmentioning
confidence: 89%
“…157 Interestingly, other studies using a polyclonal antibody reported napsin A expression in none of 49 nonpulmonary mucinous adenocarcinomas 155,156 ; thus, the low specificity reported in the former study may be attributed to its particular IHC platform. 157,164 Further, nonspecific labeling with polyclonal napsin A in mucinous adenocarcinomas appears to have peculiar supranuclear localization, as opposed to the pan-cytoplasmic granular staining present with monoclonal napsin A, possibly owing to cross-reaction with panmucin antigen by the polyclonal antibody (see Fig. 14).…”
Section: Salivary Gland-type Tumorsmentioning
confidence: 98%
“…In our patient, antibiotic treatment failure, the presence of atypical cells, and nonresolving consolidation raised concern for an unusual pattern of metastatic disease and a primary pulmonary adenocarcinoma. Studies have described high positive predictive values in diagnosing primary pulmonary adenocarcinoma with individual positivity of either TTF-1 (72%) or napsin A (83%) and higher specificity when positivity was demonstrated with both markers [26] , [27] , [28] . Our patient was negative for TTF-1 and napsin A, making primary pulmonary adenocarcinoma very unlikely.…”
Section: Discussionmentioning
confidence: 99%